Cytotopic (Cyto-) IL-15 as a New Immunotherapy for Prostate Cancer: Recombinant Production in Escherichia coli and Purification - Esteves, Ana M.; Papaevangelou, Efthymia; Smolarek, Dorota; Dasgupta, Prokar; Galustian, Christine (Frontiers in Molecular Biosciences, 2021)
Interleukin-15 (IL-15) is a cytokine previously suggested as a potential immunotherapy for cancer treatment. IL-15 can effectively reduce tumor growth in many preclinical tumor models including prostate cancer. This is due to its ability to expand and activate immune cells, such as CD8+ T cells and natural killer cells. To increase the potency of IL-15, we have engineered a protein variant that can be modified to localize and be retained in tissues where it is administered. However, the production of recombinant IL-15, the purity, and correct refolding of the final protein is not always ideal. In the current study, we aimed to optimize the methodology for production and purification of a modified recombinant human IL-15 and investigate the efficacy of the produced protein in the treatment of prostate tumors. Human IL-15 with its polypeptide sequence modified at the C-terminus to enable thiol conjugation with membrane localizing peptides, was produced in E. coli and purified using mild denaturing conditions (2M urea) from a washing step or from solubilization of inclusion bodies. The purified protein from the wash fraction was conjugated to a myristoylated peptide to form a membrane-localizing IL-15 (cyto-IL-15). The efficacy of cyto-IL-15 was investigated in subcutaneous TRAMP-C2 prostate tumors in mice and compared with cyto-IL-15 derived from protein purified from inclusion bodies (cyto-IL-15 Gen). When mild denaturing conditions were used for purification, the largest amount of IL-15 was collected from the wash fraction and a smaller amount from inclusion bodies. The protein from the wash fraction was mainly present as a monomer, whereas the one from inclusion bodies formed homodimers and higher complexes. After cytotopic modification, the purified IL-showed great efficacy in delaying prostate tumor growth (~50%) and increased mice survival by ~1.8-fold compared with vehicle. This study demonstrates an alternative, inexpensive and efficient method to produce and purify a modified version of IL-15 using mild denaturing conditions. This IL-15, when cytotopically modified, showed great efficacy as a monotherapy in prostate tumors in mice further highlighting the potential of IL-15 as a cancer immunotherapy.